DIGITAL STORYTELLING IN INCREASING ELEMENTARY SCHOOL STUDENTS’ MATHEMATICS LEARNING MOTIVATION - Amita, Nindy (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Mathematic is one of the learning subjects avoided to learn by most students in class. A perception that mathematics is a difficult and uninteresting learning subject is often embedded in students' minds so it influences their motivation in learning. Motivation can influence students’ achievement in learning. The digital era directs students to learn through technology. Through technology, students can have an improvement in motivation. This research is designed to determine whether digital storytelling has effectiveness in increasing students’ motivation or not, especially in learning mathematics. The research subjects involved five fifth-grade students at public elementary school X. The subjects were around 9-10 years old. The research used experimental techniques by observing time sampling before and after giving treatment. The research results indicate the results of the Wilcoxon normality test and obtained a value of 0.038 <0.05. There is a significant improvement for students in their learning motivation after giving the treatment, namely digital storytelling. This research can be used as a study or reference for teachers in increasing students’ motivation in class, especially in mathematics.